2014
DOI: 10.1016/j.jhep.2014.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Individual exome analysis in diagnosis and management of paediatric liver failure of indeterminate aetiology

Abstract: Background & Aims In children with liver failure, as many as half remain of indeterminate etiology. This hinders timely consideration of optimal treatment options. We posit that a significant subset of these children harbor known inherited metabolic liver diseases with atypical presentation or novel inborn errors of metabolism. We investigated the utility of whole-exome sequencing in three children with advanced liver disease of indeterminate etiology. Methods Patient 1 was a 10 year-old female diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 27 publications
1
55
0
Order By: Relevance
“…Infrequent manifestations occurring in less than 10% of affected individuals are dystonia, ataxia, retinopathy, nystagmus, corneal anesthesia and ulcers, renal tubulopathy, nephrocalcinosis, and hypoparathyroidism. In addition, three affected individuals developed hepatocellular carcinoma between ages 7 and 11 years (El‐Hattab et al., ; Karadimas et al., ; Vilarinho et al., ) (Table and and ).…”
Section: Clinical and Biochemical Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrequent manifestations occurring in less than 10% of affected individuals are dystonia, ataxia, retinopathy, nystagmus, corneal anesthesia and ulcers, renal tubulopathy, nephrocalcinosis, and hypoparathyroidism. In addition, three affected individuals developed hepatocellular carcinoma between ages 7 and 11 years (El‐Hattab et al., ; Karadimas et al., ; Vilarinho et al., ) (Table and and ).…”
Section: Clinical and Biochemical Featuresmentioning
confidence: 99%
“…To date, 75 individuals with MPV17 ‐related mtDNA maintenance defect have been reported with 39 different MPV17 pathogenic variants (Al‐Hussaini et al., ; Al‐Jasmi, Penefsky, & Souid, ; AlSaman, Tomoum, Invernizzi, & Zeviani, et al., ; Bijarnia‐Mahay, Mohan, Goyal, & Verma, ; Bitting & Hanson, ; Blakely et al., ; Choi et al., ; El‐Hattab et al., ; Garone et al., ; Kaji et al., ; Karadimas et al., ; Kim et al., ; McKiernan et al., ; Mendelsohn et al., ; Merkle, Nascene, & McKinney, ; Navarro‐Sastre et al., ; Nogueira et al., ; Piekutowska‐Abramczuk et al., ; Sarkhy, Al‐Sunaid, Abdullah, AlFadhel, & Eiyad, ; Spinazzola et al., , ; Uusimaa et al., ; Vilarinho et al., ; Wong et al., ). In this report, we present additional 25 affected individuals and nine novel MPV17 pathogenic variants.…”
Section: Introductionmentioning
confidence: 99%
“…One example of an unmet medical need is idiopathic liver disease, which remains a challenge in both pediatric and adult hepatology. We and others have shown the utility of whole-exome sequencing in the diagnosis of such patients (2)(3)(4)(5)(6). Children with unexplained liver disease who are the offspring of a consanguineous union are excellent candidates for recessive disease-causing mutations.…”
mentioning
confidence: 99%
“…Additionally, 7 individuals—who were not included in this study—have been reported in the literature with a comparable course of disease (Table 1, Supplementary Table 3) 3, 18, 26…”
Section: Discussionmentioning
confidence: 99%